Dynamic combinatorial mass spectrometry leads to inhibitors of a 2-oxoglutarate-dependent nucleic acid demethylase. - Woon, E; Demetriades, M; Bagg, E; Aik, W; Krylova, S; Ma, J; Chan, M; Walport, L; Wegman, D; Dack, K; McDonough, M; Krylov, SN; et al. (2012)
2-Oxoglutarate-dependent nucleic acid demethylases are of biological interest because of their roles in nucleic acid repair and modification. Although some of these enzymes are linked to physiology, their regulatory roles are unclear. Hence, there is a desire to develop selective inhibitors for them; we report studies on AlkB, which reveal it as being amenable to selective inhibition by small molecules. Dynamic combinatorial chemistry linked to mass spectrometric analyses (DCMS) led to the identification of lead compounds, one of which was analyzed by crystallography. Subsequent structure-guided studies led to the identification of inhibitors of improved potency, some of which were shown to be selective over two other 2OG oxygenases. The work further validates the use of the DCMS method and will help to enable the development of inhibitors of nucleic acid modifying 2OG oxygenases both for use as functional probes and, in the longer term, for potential therapeutic use.